Pengaruh Penggunaan Gadget terhadap Hasil Belajar Siswa di SMA Negeri 2 Gunungsitoli - Boy Ricardo Zega; Agnes Renostini Harefa (Departement of Mathematics Education, 2023)
Gadgets are tools that can be used to receive, search and obtain various sources of information from outside with a wide range of information. The purpose of this research is to analyze how student learning outcomes at SMA Negeri 2 Gunungsitoli are influenced by the use of technology. The type of research used is descriptive quantitative research. The population in this study were 387 students at SMA Negeri 2 Gunungsitoli and the sample was determined using a non-probability type with a purposive sampling technique of 197 people with a significant level of 5%. Data collection techniques used are observation, documentation and questionnaires. For data processing, namely conducting validity tests, reliability tests, and correlation tests. The results of the study show that there is a negative effect of using gadgets on student learning outcomes at SMA Negeri 2 Gunungsitoli. Through testing the hypothesis with the correlation test obtained t-table of 0.1398 so that t-count = 0.147989 > t-table = 0.1398.